Tagetes erecta mediated phytosynthesis of silver nanoparticles: an eco-friendly approach - UMESH P. DHULDHAJ; SHIVAJI D. DESHMUKH; ANIKET K GADE; MADHU YASHPAL; MAHENDRA K. RAI (Smujo International, 2012)
Abstract. Dhuldhaj UP, Deshmukh SD, Gade AK, Yashpal M, Rai MK. 2012. Tagetes erecta mediated phytosynthesis of silver nanoparticles: an eco-friendly approach. Nusantara Bioscience 4: 109-112. Nanotechnology is a multidisciplinary field having applications in various fields like medicine, pharmacy, engineering, and biotechnology. An important step in nanotechnology is to develop simple and eco-friendly method for the nanomaterial synthesis. Here we describe simple and eco-friendly method for synthesis of silver nanoparticles by extract of Tagetes erecta plant leaves. The phytosynthesis (synthesis by plant) of silver nanoparticles was detected by color change from light-green to dark-brown. Synthesis of silver nanoparticles was confirmed by UV-Vis spectrophotometry, further characterization includes nanoparticle tracking analysis system (NTA) (LM20) and transmission electron microscopy (TEM). TEM analysis confirms the synthesis of the polydispersed spherical silver nanoparticles of 20-50 nm, with an average size of 30 nm.